Added value of prone CT in the assessment of honeycombing and classification of usual interstitial pneumonia pattern. Issue 91 (June 2017) - Kim, Minjae; Lee, Sang Min; Song, Jae-Woo; Do, Kyung-Hyun; Lee, Hyun Joo; Lim, Soyeoun; Choe, Jooae; Park, Kye Jin; Park, Hyo Jung; Kim, Hwa Jung; Seo, Joon Beom
Highlights: Interobserver agreement of honeycombing identification was only fair. Additional prone images improved interobserver agreement of UIP classification. Prone CT conferred improvement in UIP classification for trainee radiologists. The accuracies between the supine and combined set were not different. Abstract: Objective: To retrospectively investigate whether prone CT improves identification of honeycombing and classification of UIP patterns in terms of interobserver agreement and accuracy using pathological results as a reference standard. Materials and methods: Institutional review board approval with waiver of patients' informed consent requirement was obtained. HRCTs of 86 patients with pathologically proven UIP, NSIP and chronic HP between January 2011 and April 2015 were evaluated by 8 observers. Observers were asked to review supine only set and supine and prone combined set and determine the presence of honeycombing and UIP classification (UIP, possible UIP, inconsistent with UIP). The diagnosis was regarded as correct when UIP pattern on CT corresponded to pathological UIP. Results: Interobserver agreement of honeycombing identification among radiologists was only fair on the supine and combined set (weighted κ = 0.31 and 0.34). Additional review of prone images demonstrated a significant improvement in interobserver agreement (weighted κ ) of UIP classification from 0.25 to 0.33. Prone CT conferred a significant improvement in interobserver agreement of UIP classification for trainee radiologists (from 0.10 to 0.34) while no improvement was found for board-certified radiologists (from 0.35 to 0.31). There were no significant differences in the accuracy of UIP pattern with reference to pathological results between the supine and combined set (78.8% (145/184) and 81.3% (179/220), P = 0.612). Conclusion: Additional review of prone CT can improve overall interobserver agreement of UIP classification among radiologists with variable experiences, particularly for less experienced radiologists, while no improvement was found in honeycombing identification.